2011
DOI: 10.1590/s0101-28002011000200003
|View full text |Cite
|
Sign up to set email alerts
|

A qualidade de vida dos pacientes renais crônicos em hemodiálise na região de Marília, São Paulo

Abstract: Introduction: Hemodialysis is responsible for significant alterations in the quality of life of chronic renal patients. Objective: To compare the quality of life of patients on hemodialysis without depression (A) and those with some level of depression (B). Methods: This was a transversal and descriptive study in which the Beck Depression Inventory (BDI) and the WHOQOL-bref scale were used. Results: The studied sample consisted of 130 patients, 65.15% in A, and 33.84% in B. The highest levels of depression wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
9
0
17

Year Published

2013
2013
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(26 citation statements)
references
References 8 publications
0
9
0
17
Order By: Relevance
“…First, the average HD patient has a burden of 10 symptoms that lowers overall QoL on average by an amount between 14.6 points (based on mean severity of 3.1 per symptom) or 17.6 points (based on symptom prevalence) relative to a person with no symptoms. Second, studies [26,[61][62][63][64] suggest that decreased QoL is closely related to patient mortality. Consequently, systematic evaluation of the symptom experience of HD patients seems necessary in order to develop specific interventions aimed at reducing symptom frequency and severity.…”
Section: Discussionmentioning
confidence: 99%
“…First, the average HD patient has a burden of 10 symptoms that lowers overall QoL on average by an amount between 14.6 points (based on mean severity of 3.1 per symptom) or 17.6 points (based on symptom prevalence) relative to a person with no symptoms. Second, studies [26,[61][62][63][64] suggest that decreased QoL is closely related to patient mortality. Consequently, systematic evaluation of the symptom experience of HD patients seems necessary in order to develop specific interventions aimed at reducing symptom frequency and severity.…”
Section: Discussionmentioning
confidence: 99%
“…(16) The average duration of hemodialysis concerning the participants was 40.7 (±52.3) months, ranging from two to 295. A study conducted at a Replacement Renal Therapy Unit located in the countryside of Sao Paulo state, with the purpose of characterizing the elderly with chronic kidney disease undergoing hemodialysis and assessing the hope levels through the Herth Hope Scale, identified that it ranged from one and 132 months.…”
Section: Discussionmentioning
confidence: 99%
“…The conditions which lead patients to depression involve physiological and psychological aspects of treatment 22 , such as HD dependence, fear of death and physical complications of the disease 23 .…”
Section: Discussionmentioning
confidence: 99%